THE INFLUENCE OF ENTREPRENEURIAL ORIENTATION, MARKET ORIENTATION, AND INNOVATION ON COMPETITIVE ADVANTAGE - Nurfauziah, Syafa; Mukhsin, Moh; Ganika, Gerry (Journal of Management Small and Medium Enterprises (SMEs), 2025)
The purpose of this study was to determine the effect of entrepreneurial orientation, market orientation, and product innovation on competitive advantage. This research uses quantitative methods and uses purposive sampling techniques by distributing 83 questionnaires to MSMEs of various cakes in Koja District, North Jakarta. The analysis method used is Multiple Linear Regression. Based on the results, competitive advantage is positively and significantly impacted by entrepreneurial approach and product innovation, but not significantly by market orientation. With an R-Square value of 0.7, it can be concluded that entrepreneurial orientation, market orientation, and product innovation affect competitive advantage by 70% and the remaining 30% is influenced by other variables. It is recommended to expand the scope of data so that future research provides a more comprehensive and accurate picture of competitive advantage in MSMEs. Keywords : Entrepreneurial Orientation ; Market Orientation ; Product Innovation; Competitive Advantage